Badania diagnostyczne w glottodydaktyce – zalety i trudności - Mihułka, Krystyna (Neofilolog, 2010)
The purpose of the following article is to discuss the theoretical framework of diagnostic research used in glottodidactics as well as to analyze some selected diagnostic studies conducted by Polish and German researchers in the last decade into the development of high school and university students’ and foreign language teachers’ intercultural competence. In the last part of this article attention is paid to the presentation and discussion of the most frequent problems which researchers encounter while planning and carrying out diagnostic studies.